2019
DOI: 10.1002/eji.201948286
|View full text |Cite
|
Sign up to set email alerts
|

LCMV‐specific CD4 T cell dependent polyclonal B‐cell activation upon persistent viral infection is short lived and extrafollicular

Abstract: Persistent virus infections with non‐ or poorly cytopathic viruses are commonly associated with B cell dysregulations. These include the induction of hypergammaglobulinemia and the emergence of virus‐unspecific antibodies. These seemingly unspecific antibody responses interfere with the virus‐specific humoral immunity and contribute to delayed virus control. Whether these virus‐unspecific antibodies are induced in the B cell follicle or at extrafollicular sites and whether one specific CD4 T cell subset is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…ELISA confirmed that all three tested variants maintained NP specificity with comparable signals to the previously tested variant and our positive control antibody (Figures 6C, S11A). Surprisingly, when screened for specificity against other antigens (LCMV GPC, insulin, dsDNA, DNP-OVA, lysate of uninfected and infected cells), we discovered that two of the variants specifically bound DNP-OVA but not the other tested LCMV-unrelated antigens (Figures 6D, S12), thereby providing a potential explanation for the LCMV-unspecific IgG antibody response characteristic of chronic viral infection (Greczmiel et al, 2020). Sequence analysis revealed that the three variants had incurred multiple somatic hypermutations, preferentially in their CDRH2 relative to the most expanded variant and reference germline (Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISA confirmed that all three tested variants maintained NP specificity with comparable signals to the previously tested variant and our positive control antibody (Figures 6C, S11A). Surprisingly, when screened for specificity against other antigens (LCMV GPC, insulin, dsDNA, DNP-OVA, lysate of uninfected and infected cells), we discovered that two of the variants specifically bound DNP-OVA but not the other tested LCMV-unrelated antigens (Figures 6D, S12), thereby providing a potential explanation for the LCMV-unspecific IgG antibody response characteristic of chronic viral infection (Greczmiel et al, 2020). Sequence analysis revealed that the three variants had incurred multiple somatic hypermutations, preferentially in their CDRH2 relative to the most expanded variant and reference germline (Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
“…Induction of PHGG is mediated by LCMV-specific non-follicular CD4 helper cells, which support the activation of B cells in a B-cell receptor independent manner. For instance, LCMV infection results in plasma cells producing antibodies specific to unrelated antigens such as ovalbumin and dinitrophenol (DNP) or autoantigens (i.e., double- and single-stranded DNA, insulin or thyroglobulin) (Greczmiel et al, 2020; Hunziker et al, 2003), whereby these autoantibody titers can even be comparable to the concomitantly induced antiviral antibody response (Ludewig et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…5B). Other studies show that persistent virus infections are associated with B-cell dysregulations, and CHC patients have the risk to develop mixed cryoglobulinemia which is associated with B-cell proliferative disorder and Bcell non-Hodgkin's lymphoma (B-NHL) [31][32][33]. We speculated that CD19scFv might inhibit B-cell proliferative disorder caused by chronic HCV infection.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, LCMV Cl13, which produces chronic infection, induces higher and more sustained PD-1 upregulation in T cells, and PD-1/PD-L1 interaction significantly contributes to T cell suppression and viral persistence ( 45 ). Interestingly, LCMV infection also triggers polyclonal B cell activation ( 46 , 47 ). Given that virus-specific CD4 + and CD8 + T cells from LCMV Cl13- (but not ARM-)-infected mice express high levels of PD-1 ( 45 ), it is tempting to speculate that PD-L1 hi plasmablasts may also contribute to suppressing antiviral T cells during chronic LCMV infection.…”
Section: Discussionmentioning
confidence: 99%